POLITIK DAN HEGEMONI DALAM PENGUNDURAN DIRI TUAN RUMAH PIALA DUNIA FIFA U-20 INDONESIA - Wijaya, Gustaf; Amarta Prayoga, Reza; Nurul Hakim, Fatwa; Solekha, Nuzul; Ririn Purba (The Journal of Society and Media, 2025)
Indonesia has one of football's biggest fan bases. This study explores public reactions to Indonesia losing its U-20 World Cup hosting status. It aims to: 1) trace responses on Twitter, 2) analyze reactions from national figures opposing the Israeli team, and 3) examine public sentiments towards FIFA's influence. The removal sparked mixed reactions, affecting the image of various political figures in Indonesia. Data was gathered through content analysis of 5,000 tweets from March 30 to April 7, 2023, focusing on comments related to the U-20 World Cup. The findings indicated that the public predominantly criticized political figures who opposed hosting the event, mainly due to the controversy surrounding the Israeli national team’s participation. The 2023 FIFA cancellation coincided with a significant political moment in Indonesia, where GP and IWK, from the PDI-P party, opposed the Israeli team's participation in FIFA, citing support for Palestine. In contrast, ET, as both PSSI chairman and Minister of State-Owned Enterprises, aimed to maintain Indonesia's reputation in the football community. This rejection led to public backlash against GP, ET, and IWK, negatively impacting their popularity, particularly GP's presidential electability. The lack of a detailed explanation behind FIFA's decision highlights its global authority in football